Whole‐exome sequencing identified novel variants in three Chinese Leigh syndrome pedigrees. Issue 4 (10th January 2022) - Yang, Zhihua; Cao, Jun; Song, Yucen; Li, Suyi; Jiao, Zhihui; Ren, Shumin; Gao, Xu; Zhang, Suqin; Liu, Jingjing; Chen, Yibing
Abstract: Leigh syndrome (LS), the most common mitochondrial disease in early childhood, usually manifests variable neurodegenerative symptoms and typical brain magnetic resonance imaging (MRI) lesions. To date, pathogenic variants in more than 80 genes have been identified. However, there are still many cases without molecular diagnoses, and thus more disease‐causing variants need to be unveiled. Here, we presented three clinically suspected LS patients manifesting neurological symptoms including developmental delay, hypotonia, and epilepsy during the first year of age, along with symmetric brain lesions on MRI. We explored disease‐associated variants in patients and their nonconsanguineous parents by whole‐exome sequencing and subsequent Sanger sequencing verification. Sequencing data revealed three pairs of disease‐associated compound heterozygous variants: c.1A>G (p.Met1?) and 409G>C (p.Asp137His) in SDHA, c.1253G>A (p.Arg418His) and 1300C>T (p.Leu434Phe) in NARS2, and c.5C>T (p.Ala2Val) and 773T>G (p.Leu258Trp) in ECHS1 . Among them, the likely pathogenic variants c.409G>C (p.Asp137His) in SDHA, c.1300C>T (p.Leu434Phe) in NARS2, and c.773T>G (p.Leu258Trp) in ECHS1 were newly identified. Segregation analysis indicated the possible disease‐causing nature of the novel variants. In silico prediction and three‐dimensional protein modeling further suggested the potential pathogenicity of these variants. Our discovery of novel variants expands the gene variant spectrum of LS and provides novel evidence for genetic counseling.